A human rights-based approach to child labour in Africa : challenges and prospects in South Africa - Vukor-Quarshie, G.N.K. (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.